Randomized, placebo‐controlled study on the effects of intravenous GSK3858279 (anti‐CCL17) on a battery of evoked pain tests in healthy participants - Yvonne Boyle; Hemme J. Hijma; Jamie Rees; Jagtar Nijjar; Eirini Panoilia; Yolanda Alvarez; Sarah Siederer; Emma Greening; Edward Emery; Kathy Abbott Banner; Geert Jan Groeneveld (Wiley, 2024)
Abstract C-C Motif Chemokine Ligand 17 (CCL17) is a chemokine that binds and signals through the G‐protein coupled CC‐chemokine receptor 4 and has been implicated in the development of inflammatory and arthritic pain. GSK3858279 is a high‐affinity, first‐in‐class, monoclonal antibody, binding specifically to CCL17 and inhibiting downstream signaling. In this phase I, randomized, single‐center, double‐blind, placebo‐controlled, three‐period, incomplete‐block crossover study (NCT04114656), the analgesic effects and safety of intravenous GSK3858279 were assessed in a battery of evoked acute pain assessments on healthy, adult (aged ≥18 years), male participants. Participants were randomized 1:1 to receive either one placebo (0.9% w/v NaCl) dose followed by two GSK3858279 doses (PAA treatment sequence), or one GSK3858279 dose followed by two placebo doses (APP treatment sequence). The co‐primary end points were ultraviolet B heat pain detection threshold (°C), cold pressor time to pain tolerance threshold (PTT, sec), and electrical PTT (mA, single stimulus). Twenty‐one participants were enrolled (PAA = 11; APP = 10). Mean age (standard deviation) was 29.3 (7.9) years for PAA, 31.1 (7.7) years for APP. No significant differences were observed in the analgesic effect between GSK3858279 and placebo for any end point. Exposure to GSK3858279 was similar between Period 1 (APP sequence), and Periods 2 and 3 (PAA sequence), with some GSK3858279 carry‐over. Changes in serum CCL17 levels were consistent with the expected GSK3858279 activity. All drug‐related adverse events were mild in intensity and caused no discontinuations. The absence of an efficacy signal in this acute pain model does not preclude efficacy in chronic pain states.